2014
DOI: 10.1111/j.1365-4632.2012.05771.x
|View full text |Cite
|
Sign up to set email alerts
|

Menstrual irregularities, fertility status, and ovarian function in female patients with leprosy in India

Abstract: Multibacillary leprosy may be associated with menstrual irregularities and elevation of gonadotropin hormones, indicating an ovarian dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…In a study from India by Khanna et al (2014), a significantly larger number of female patients with MB leprosy had irregular periods postdating the onset of leprosy than patients with PB leprosy. The study also found that gonadotropic hormone levels were elevated in significantly more patients with MB leprosy vis-à-vis patients with PB leprosy, and that the mean levels of these hormones showed an increasing trend from controls to patients with PB to patients with MB leprosy.…”
Section: Effect Of Leprosy On Menstrual Cycle and Fertility Statusmentioning
confidence: 95%
“…In a study from India by Khanna et al (2014), a significantly larger number of female patients with MB leprosy had irregular periods postdating the onset of leprosy than patients with PB leprosy. The study also found that gonadotropic hormone levels were elevated in significantly more patients with MB leprosy vis-à-vis patients with PB leprosy, and that the mean levels of these hormones showed an increasing trend from controls to patients with PB to patients with MB leprosy.…”
Section: Effect Of Leprosy On Menstrual Cycle and Fertility Statusmentioning
confidence: 95%